Account Security using Randomized 3D Environment Image (International Journal of Scientific Research and Management (IJSRM), 2015)
3D environment image with random textual password is a new scheme of authentication. This scheme is based on a virtual threedimensional environment. To be authenticated, I present a 3-D virtual environment where the user navigates and interacts with various objects. The sequence of actions and interactions toward the objects inside the 3-D environment constructs the user’s 3-D password. The 3-D password can combine most existing authentication schemes such as textual passwords, graphical passwords into a 3-D virtual environment. The design of the 3-D virtual environment and the type of objects selected determine the 3-D password key space. The objects and actions contain in 3-D virtual environment specify some random keyword for each at every login. This provides more authenticated technique.